2021
DOI: 10.3390/plants10040682
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Conditions for Microwave-Assisted Extraction of Polyphenolic Content and Antioxidant Activity of Barleria lupulina Lindl.

Abstract: Barleria lupulina Lindl. (Acanthaceae) as an ornamental plant has been widely used in folklore medicine due to its abundancy in polyphenolic compounds. The present study examined conditions for optimal extraction of antioxidants from B. lupulina leaf extracts by using the microwave-assisted extraction (MAE) method. The effects of ethanol concentrations, microwave power, and extraction time on total phenolic content (TPC), total flavonoid content (TFC), 1-diphenyl-2-picrylhydrazyl (DPPH), and 2,20-azino-bis (3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
13
2
Order By: Relevance
“…Notably, at the 50% ethanol concentration, an increase in temperature gave a negative effect on the IC 50 value, where the reading increased to nearly 700 µg/mL. Contrary to a previous report on Barleria lupulina extracts [40], free radical scavenging activity was reduced with increasing ethanol concentration, while it was significantly increased with a prolonged extraction time. Although a longer extraction time might increase the quantity of extracted analytes [41], there is a possibility that the extracted compounds are degraded during the process.…”
Section: Ic 50 Valuecontrasting
confidence: 69%
“…Notably, at the 50% ethanol concentration, an increase in temperature gave a negative effect on the IC 50 value, where the reading increased to nearly 700 µg/mL. Contrary to a previous report on Barleria lupulina extracts [40], free radical scavenging activity was reduced with increasing ethanol concentration, while it was significantly increased with a prolonged extraction time. Although a longer extraction time might increase the quantity of extracted analytes [41], there is a possibility that the extracted compounds are degraded during the process.…”
Section: Ic 50 Valuecontrasting
confidence: 69%
“…The maximum content obtained was 288.88 ± 0.016 mg GAE ⋅ g −1 at 480 W and 60 s, and the least was 151.22 ± 0.055 mg GAE ⋅ g −1 extract at 600 W and 90 s. Increasing microwave power can improve extraction efficiency by boosting molecular interactions between the electromagnetic field and the sample. Longer exposure to a higher microwave power, on the other hand, may destroy some phenolic compounds (Ismail-Suhaimy et al, 2021). In the present study, lower TPC was achieved corresponding to microwave power >480 W and time >60 s. It appears that a lower power is not efficient for extraction of phenolics while a higher power may result in the degradation of these substances (Lovrić et al, 2017;Abbas et al, 2021).…”
Section: Total Phenolic Contentcontrasting
confidence: 42%
“…Microwave power was also a significant parameter (p ≤ 0.01) in the MAE of polyphenols from Laurus nobilis L. leaves. The total phenolic content of the extracts was lower when 800 W was applied compared to 400 W. Other authors also reported a decrease in total phenolic content in extracts of different plant material when microwave power higher than 600 W was applied [16,[41][42][43].…”
Section: Microwave-assisted Extraction (Mae) Optimizationmentioning
confidence: 89%
“…extracts obtained with 60% ethanol in comparison to 50% ethanol. In addition, Ismail-Suhaimy et al (2021) [42] reported an increase in total phenolic content of Barleria lupulina L. extracts with the increase in ethanol concentration from 40% to 80%. On the other hand, Dahmoune et al (2015) [43] observed a decline in total phenolic content in Myrtus communis L. leaf extracts with the increase in ethanol concentration from 40% to 60%.…”
Section: Microwave-assisted Extraction (Mae) Optimizationmentioning
confidence: 97%